GAMBARAN STEREOTIP UMAT KATOLIK PERKOTAAN DI MALUKU ATAS HIDUP DAN PELAYANAN IMAM DIOSESAN - Batlayeri, Willem; Ngutra, Seno; Deo, Adri (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2018)
The Diocesan priests are the main ministers of the apostolic ministry and faith development of the people in every diocese. The effort to implement the spiritual apostolate in the midst of the people of God, the diocesan priests are often received the negative assessment from the people. The history has noted that from of old the people of the compare the life style and the ministry of the diocesan priests and the religious priests. The religious priests are assessed to be better than the diocesan priests. This common assessment also takes place in the diocese of Amboina. However, if we are wise enough, this assesements become the input for the betterment of the spiritual grouth of the diocesan priests.